Two Rationally Identified Novel Glitazones Reversed the Behavioral Dysfunctions and Exhibited Neuroprotection Through Ameliorating Brain Cytokines and Oxy-Radicals in ICV-LPS Neuroinflammatory Rat Model - Justin, Antony; Ashwini, Premkumar; Jose, Jincy A.; Jeyarani, Victoria; Dhanabal, S. P.; Manisha, Chennu; Mandal, Subhankar P.; Bhavimani, Guru; Prabitha, P.; Yuvaraj, S.; Prashantha Kumar, B. R. (Frontiers in Neuroscience, 2020)
The present study has planned to evaluate the neuroprotective activity of two novel glitazones in a neuroinflammatory rat model. Two novel glitazones were selected from an in-house virtual library of glitazones based on their docking scores against peroxisome proliferator-activated receptor-gamma (PPAR-γ) protein and other parameters studied in in silico computational studies. Initially, an acute oral toxicity study was carried out for glitazones in rats to assess the toxicity profile and to determine the therapeutic range for neuroprotective evaluation. Prior to induction of neuroinflammation, the treatments with glitazones (G1 and G2) and standard pioglitazone were made for four consecutive days to respective groups. On the fifth day, the neuroinflammation was induced by intracerebroventricular (ICV) administration of lipopolysaccharides (LPS) (2 μg/μl) using stereotaxic apparatus. After 7 days, the rats were subjected to behavioral assessment followed by neurobiochemical evaluation and histopathological studies. The pre-treatment with glitazones at two dose levels (15 and 30 mg/kg) has significantly reversed behavioral dysfunctions. Glitazones have shown significant reduction in the levels of LPO, NO, TNF-α, and IL-1β and also increased the levels of antioxidant enzymes such as SOD, CAT, and GSH in the brain of LPS-administered rats. The neuroprotection exhibited by two novel glitazones is comparable with standard pioglitazone. The PPAR-γ-dependent amelioration of cytokines and oxy-radicals released by novel glitazones during neuroinflammatory conditions may be attributed to the reversal of behavioral dysfunctions through preventing the degeneration of neurons in major regions of the brain.